'A miracle. Madonna!': Irony in the representation of Alitalia's privatization by the Italian, British and American press. (May 2013) - Fusari, Sabrina
This article focuses on irony in the representation of the privatization of the Italian airline, Alitalia, in the Italian, British and American press. We rely on a previous study (Fusari, 2010, 2011a) of the metaphors found in three electronic corpora containing all the articles published on this event by Repubblica and Corriere della Sera in Italian, The Guardian, The Times and the Financial Times in British English, and The New York Times and the Washington Post in American English, during the six months (August 2008–January 2009) that led to Alitalia's acquisition by Compagnia Aerea Italiana (CAI), a private consortium of Italian investors. The analysis also focuses on the Italian translation of a Financial Times article which appeared in Corriere della Sera . Through the use of undertranslation, which involves the elimination of a crucial metonymy, the criticism of the Financial Times 's irony is considerably reduced in Italian.